A novel numerical technique to enhance the spatial resolution of electrical impedance tomography systems - Chitturi V.; Nagi F.H. (Research India Publications, 2023)
Electrical impedance tomography (EIT) has shown significant results as a functional imaging tool. However, it is not yet fully suitable for anatomical imaging because of its poor spatial resolution. In this study, the anatomical information of the test object is obtained in the form of the boundary potentials using an EIT system. Then, the electrical conductivity/permittivity distribution within the test object is approached by the Laplacian difference equations and later solved by Liebmanns method. Valid results are visible with an underlying assumption of the electrical potential at the center of the test object. This novel technique provides more accurate readings and also converges to a stable solution faster. Accuracy from 99.555% to 99.785% is obtained within six iterations as compared to the traditional technique where the accuracy range from 99.265% to 99.630% with eight iterations for ?a ? 1%. This is first step towards better spatial resolution for the EIT systems. Research India Publications.